2007
DOI: 10.21273/jashs.132.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Late Blight Resistance of RB Transgenic Potato Lines

Abstract: Late blight of potato (Solanum tuberosum L.), incited by Phytophthora infestans (Mont.) de Bary, is a devastating disease affecting tuber yield and storage. Recent work has isolated a resistance gene, RB, from the wild species Solanum bulbocastanum Dun. Earlier work in Toluca, Mexico, observed significant levels of field resistance under intense disease pressure in a somatic hybrid containing Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 37 publications
1
16
0
6
Order By: Relevance
“…Thus, improvement of specific traits in popular processing cultivars using genetic engineering could be a highly effective, rapid, and economical approach for potato improvement. The potential of this approach has been well demonstrated by genetic engineering for several important potato traits including resistance to potato late blight (Halterman et al, 2008; Kuhl et al, 2007) and high‐amylose starch (Schwall et al, 2000). Genetically modified low amylose potatoes were approved for commercial release in Europe in 2010 (Ryffel, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, improvement of specific traits in popular processing cultivars using genetic engineering could be a highly effective, rapid, and economical approach for potato improvement. The potential of this approach has been well demonstrated by genetic engineering for several important potato traits including resistance to potato late blight (Halterman et al, 2008; Kuhl et al, 2007) and high‐amylose starch (Schwall et al, 2000). Genetically modified low amylose potatoes were approved for commercial release in Europe in 2010 (Ryffel, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Besides classical breeding, the cloning of Rpi-blb1/RB has opened the possibility of producing resistant potatoes with increased resistance to late blight by direct transfer of the gene using recombinant DNA techniques (70). However, the exploitation of Rpi-blb1 may be complicated by the observation that when introduced into cultivated potato, this gene confers only partial resistance to aggressive isolates.…”
Section: Rpi-blb1mentioning
confidence: 99%
“…No known isolates were virulent on both wild species and none had been identified that were able to overcome all three R genes (Vleeshouwers and Oliver, 2014;Vleeshouwers et al, 2011). The RB gene, also referred to as Rpi-blb1, has been shown to slow down lesion development and to confer partial field resistance to LB (Chen and Halterman, 2011;Halterman et al, 2008;Kuhl et al, 2007). A transcript dose-response was documented for resistance to foliar LB, but also for tuber resistance (Bradeen et al, 2009;Kramer et al, 2009;Millett et al, 2015).…”
Section: Introductionmentioning
confidence: 99%